An extended mechanism to prevent distributed denial of service attack in DV-Hop localisation algorithm in wireless sensor networks. Issue 2 (3rd July 2021) - Kaur, Simarjeet; Kaur, Navdeep; Bhatia, Kamaljit Singh
Distance Vector (DV)-Hop localisation scheme is one of the most successful localisation schemes. However, when network is interrupted with Distributed Denial of Service (DDoS) attack then the localisation process of DV-Hop scheme is badly affected. This paper has examined the effects of the DDoS attack on the DV-Hop algorithm. So, a mechanism consisting of swarm optimisation and machine learning is proposed to guard against DDoS attack. The architecture also designs a novel fitness function for Artificial Bee Colony (ABC). To check the effectiveness of the proposed fitness function of ABC, Neural Network with Gradient satisfaction is applied. The cross validation architecture further uses Mean Square Error (MSE) for the back propagation model and effectiveness is checked through a regression model as well. The evaluation is done in terms of Localisation error and Transmission loss. The simulation results show the reduction of 33% for localisation error and 27% for transmission loss respectively.